2019
DOI: 10.1038/s41529-019-0094-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the dissolution kinetics of silicate glasses by topology-informed machine learning

Abstract: Machine learning (ML) regression methods are promising tools to develop models predicting the properties of materials by learning from existing databases. However, although ML models are usually good at interpolating data, they often do not offer reliable extrapolations and can violate the laws of physics. Here, to address the limitations of traditional ML, we introduce a "topologyinformed ML" paradigm-wherein some features of the network topology (rather than traditional descriptors) are used as fingerprint f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 51 publications
2
60
0
Order By: Relevance
“…19,20 Various TCT-based models have been proposed over the past decades to predict glass-forming ability, glass-transition temperature, liquid fragility, hardness, stiffness, dissolution rate, etc. 19,[21][22][23][24][25][26][27][28] The success of TCT is based on the fact that many macroscopic properties of disordered materials primarily depend on the topology of the atomic structure, whereas other structural details only have a second-order effect. 29 As such, TCT reduces complex disordered atomic networks into simpler structural trusses, 22 wherein some nodes (the atoms) are connected to each other by some topological constraints (the chemical bonds).…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Various TCT-based models have been proposed over the past decades to predict glass-forming ability, glass-transition temperature, liquid fragility, hardness, stiffness, dissolution rate, etc. 19,[21][22][23][24][25][26][27][28] The success of TCT is based on the fact that many macroscopic properties of disordered materials primarily depend on the topology of the atomic structure, whereas other structural details only have a second-order effect. 29 As such, TCT reduces complex disordered atomic networks into simpler structural trusses, 22 wherein some nodes (the atoms) are connected to each other by some topological constraints (the chemical bonds).…”
Section: Introductionmentioning
confidence: 99%
“…Reported rates (n = 802 rates from 105 distinct glasses) are extracted and aggregated from 33 different papers-pulled from cement, 29,30,[33][34][35][36] geochemistry [44][45][46][47][48]50,[52][53][54][55][56] and nuclear waste and glass science 57,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] literature. While other studies have analyzed published data to discover trends and ascertain relationships between driving factors and dissolution rates 32,81 or other material properties; [82][83][84] as far as the authors are aware, this is both the largest data set specifically focused on glass dissolution and the first time such a study has tested cross-discipline relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to recent advances in computational power and robust algorithms, we have witnessed the rise of an interdisciplinary field in computational material science [6][7][8][9] . Specifically, researchers have already shown success in utilizing ML-based or other AI methods in two major categories: (1) to accelerate the prediction of material properties for specific applications [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] , and (2) to accelerate the on-demand design and the optimization of material microstructure and composition for targeted properties [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] . These promising studies have shown superior effectiveness of ML techniques compared to traditional computational modeling or experimental measurements on a variety of materials.…”
Section: Introductionmentioning
confidence: 99%